EFEKTIFITAS PENGGUNAAN BAHAN AJAR BERBASIS WEB TERHADAP HASIL BELAJAR MAHASISWA PADA MATA KULIAH EVALUASI PROSES DAN HASIL PEMBELAJARAN UNIVERSITAS BATURAJA - Yelmi Yunarti; Sulia Ningsih (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2018)
The purpose of this study was to determine the effect ivenes of web-based teaching materials on student learning achievement in the evaluation of learning process and achievement course of Baturaja University. This experimental study used one group pretest postest design. There were 32 of fifth semester students participated in this study. Testing was used to collect the data. The data was analyzed using t test and computed through SPSS 22. The results showed that the significant value was 0.000 which were less than 0,05 (0,000 < 0,05). This means that there was significant difference between students’ pretest postest scores. From the result, it could be conclude that web based teaching materials were effectively used to improve students’ learning achievement.Keywords: Web-based teaching materials, learning achievement, evaluation of learning process and achievement course